The twilight man - Moorcock, Michael, 1939-; Berkley Publishing Group (New York, N.Y. : Berkley Pub. Corp., 1970)
With Earth teetering on the brink of extinction, only one man dares to defy the legacy of the Spaceraiders - Clovis Marca, the twilight man.Long ago Earth, now fixed on her axis, with eternal day on one side, eternal night on the other and a ribbon of twilight in between, was ravaged by galactic raiders. Earthlings recovered, grew stronger. But now, unable to reproduce, the last humans are frenzied with final decadence. And fear.Only Clovis Marca, the last man born on Earth, dares to brave infected space to seek the impossible solution. His dark quest leads him to face Orland Sharvis, the scientist whose insane experiments on his own mind and body might just save the human race... but would that race then be more, or less, human?
Mode of access: Internet.
Keywords: Human-alien encounters -- Fiction; Science fiction